Mycophenolate mofetil‐related leukopenia in children and young adults following kidney transplantation: Influence of genes and drugs. (4th September 2017) - Varnell, Charles D.; Fukuda, Tsuyoshi; Kirby, Cassie L.; Martin, Lisa J.; Warshaw, Barry L.; Patel, Hiren P.; Chand, Deepa H.; Barletta, Gina‐Marie; Van Why, Scott K.; VanDeVoorde, Rene G.; Weaver, Donald J.; Wilson, Amy; et al.
Abstract: MMF is commonly prescribed following kidney transplantation, yet its use is complicated by leukopenia. Understanding the genetics mediating this risk will help clinicians administer MMF safely. We evaluated 284 patients under 21 years of age for incidence and time course of MMF‐related leukopenia and performed a candidate gene association study comparing the frequency of 26 SNPs between cases with MMF‐related leukopenia and controls. We matched cases by induction, steroid duration, race, center, and age. We also evaluated the impact of induction and SNPs on time to leukopenia in all cases. Sixty‐eight (24%) patients had MMF‐related leukopenia, of which 59 consented for genotyping and 38 were matched with controls. Among matched pairs, no SNPs were associated with leukopenia. With non‐depleting induction, UGT2B7‐900A>G (rs7438135) was associated with increased risk of MMF‐related leukopenia ( P = .038). Time to leukopenia did not differ between patients by induction agent, but 2 SNPs (rs2228075, rs2278294) in IMPDH1 were associated with increased time to leukopenia. MMF‐related leukopenia is common after transplantation. UGT2B7 may influence leukopenia risk especially in patients without lymphocyte‐depleting induction. IMPDH1 may influence time course of leukopenia after transplant.